Techno‐economic and energy assessment of building integrated photovoltaic module as an envelope of the building. (20th September 2021) - Shankar, Ajay; Vijayakumar, Krishnasamy; Chitti Babu, Baladhandautham
Summary: Buildings across the globe consume a prodigious amount of total energy generation and are held responsible for challenging the competing urge of the energy trilemma (ET). The available space for rooftop photovoltaic (PV) modules is often not adequate to cater to the entire energy demand of the buildings in an urban environment. Therefore, this article proposes a semi‐transparent building integrated photovoltaic (BIPV) module at the vertical part of the building facade for on‐site clean energy generation. The amount of incident solar irradiation at the surface of the BIPV placed at vertical tilt angles is estimated by using the solar transposition model, and the performance of the BIPV is evaluated on the indexes of ET. A coupled analysis of energy generated by the BIPV with the building energy demand is presented to analyze the reliability index ET. Economic parameters viz. cost of energy (COE) and levelized cost of energy (LCOE) are proposed to evaluate and compare the affordability index of ET associated with the BIPV and existing rooftop PV module. Further, the environmental sustainability (elimination of greenhouse gas (GHG) emissions) of the proposed BIPV module for the building is presented. Abstract : Schematic diagram of building integrated PV module with DC nanogrid.